Women empowerment of youth group through paper flower crafts in Cipayung Village - Emmelia Tan; Nur Aeni (Privietlab, 2021)
In this era of globalization, competition and the development of urban communities are getting tougher, this is due to the quality of human resources. The purpose of this service is to find out the strategies adopted by Cipayung Village in empowering women. This research method is through observation, interviews, and documentation. The results achieved from the women's empowerment program through paper flower craft training in the Women's Youth group in Cipayung Village are the addition of knowledge for members for skills capital that can be applied as entrepreneurial capital which later can create women who are independent, empowered, and able to raise their standards. live by increasing economic income for his family.